Emergency risk assessment and management (Nexo Revista Científica, 2022)
This article attempts to study the role of emergency risk management in the era of the digital economy. The main purpose of the article is to identify the major patterns that determine the features of risk assessment in business as the main element contributing to the achievement of economic security of the organization, as well as to carry out a comparative analysis of risk assessment and management methods in emergencies. The modern economic analysis employs various risk management methods. The most effective ways to reduce risk in conditions of the economic and political instability in Russia are the method of scenarios and the method of hierarchy analysis, as well as diversification, i.e. the distribution of risks between several business participants. Emergencies may have a different character depending on the nature of the adverse event. This article deals with natural and man-made emergency dangers.